The Seniors’ Mathematical Culture Maturity: Criteria, Indicators and Levels - Biliunas, Anastasiia (Pedagogical Discourse, 2014)
The attention in the article has been concentrated on the maturity of mathematical culture of senior pupils. In the course of the research the main criterion of maturity of mathematical culture of senior pupils has been determined, its sense is in advancement from the low level to the high one; indicators of the level of maturity of mathematical culture have been chosen (the amount and quality of mathematical knowledge and skills, the amount and quality of skills of of mathematical selfeducation, mastering of language of mathematical culture). In the course of forming of mathematical culture of senior pupils we singled out the following levels: initial (insufficiant) – reproductive, medium (neutral) or heuristic, sufficient and high – it is the level of productive-creative activity. The passage to the new level means qualitative leap in the mastering of knowledge, abilities and skills of of mathematical culture. These levels are offered in criteria-level table of maturity of of mathematical culture, depending on its components maturity. The received results of the ascertaining experiment have been offered.